Transcriptional Variation in Glucosinolate Biosynthetic Genes and Inducible Responses to Aphid Herbivory on Field-Grown Arabidopsis thaliana - Sato, Yasuhiro; Tezuka, Ayumi; Kashima, Makoto; Deguchi, Ayumi; Shimizu-Inatsugi, Rie; Yamazaki, Misako; Shimizu, Kentaro K.; Nagano, Atsushi J. (Frontiers in Genetics, 2019)
Recently, increasing attempts have been made to understand how plant genes function in natura. In this context, transcriptional profiles represent plant physiological status in response to environmental stimuli. Herein, we combined high-throughput RNA-Seq with insect survey data on 19 accessions of Arabidopsis thaliana grown at a field site in Switzerland. We found that genes with the gene ontology (GO) annotations of “glucosinolate biosynthetic process” and “response to insects” were most significantly enriched, and the expression of these was highly variable among plant accessions. Nearly half of the total expression variation in the glucosinolate biosynthetic genes (AOPs, ESM1, ESP, and TGG1) was explained by among-accession variation. Of these genes, the expression level of AOP3 differed among Col-0 accession individuals depending on the abundance of the mustard aphid (Lipaphis erysimi). We also found that the expression of the major cis-jasmone activated gene CYP81D11 was positively correlated with the number of flea beetles (Phyllotreta striolata and Phyllotreta atra). Combined with the field RNA-Seq data, bioassays confirmed that AOP3 was up-regulated in response to attack by mustard aphids. The combined results from RNA-Seq and our ecological survey illustrate the feasibility of using field transcriptomics to detect an inducible defense, providing a first step towards an in natura understanding of biotic interactions involving phenotypic plasticity.